MEMAHAMI SOSIOLOGI SEBAGAI REPOSISI ILMU DALAM ISLAM - Zainul Huda (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Among the weakness of human resources in Islam is rooted on the way Muslims perceived knowledge. Within the everyday life of Muslims, there are some branches of knowledge that are considered as less important. Furthermore, some conservative Muslims even see those less important knowledge as prohibited to be learnt based on Westerners domination of those knowledge and ignore the use of those knowledge for human beings. This model of perceiving knowledge has serious impact on individual as well as Muslim as the whole ummah in leading the development of knowledge in the world. This article tries to correct or at least to give a contribution in building opinion in order to provide more suitable perspective of Islam in perceiving knowledge. By employing Islam as a framework to portray the development of science in Islam is necessary in order to create awareness among Muslims on the necessity of acquiring and developing knowledge for the sake of better life for all human beings